Dynamic stereotype and its role in written language diagnostics - Shepitko, Valery (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article is devoted to the role of a dynamic stereotype in the diagnosis of written speech. Author paid attention to: 1 global processes in the exchange of information between people; 2 changes in the tool base for the texts writing; 3 the usage of electronicdocuments and electronic signatures; 4 the exchange of e-mail messages. The study of the written language in criminalistics is carried out within the framework of forensic handwriting examination judicial handwriting and forensic linguistics. The dynamic stereotype took the important place in these branches of criminalistic techniques – the neurophysiological basis of skills, a definite integral system of conditioned reflex reactions.The dynamic stereotype is also typical for various modern ways of performing texts including using of electronic information resources. Reader attention is focused on new directions in the diagnostic examination of written texts, the formation of forensic criminalistic linguistics and psycholinguistics, as well as the development of psycholinguistic study of texts for identification purposes.
Keywords: pismo odręczne; dokument elektroniczny; tekst dokumentu; kryminalistyczne badanie języka pisanego; psycholingwistyczne badanie tekstu; psycholingwistyka; językoznawstwo sądowe